Place branding in tourism: a review of theoretical approaches and management practices - Marta Almeyda-Ibáñez; Babu P. George (Tourism & Management Studies)
This paper draws from the generic literature on branding to develop the idea of tourist based destination branding. Tourist based brand equity is proposed as an alternative to the more traditional destination resource centered idea of brand equity. In that process, it identifies various tourism related nuances that obfuscate brand building. Measurement approaches to quantify destination brand equity are compared, highlighting the pros and cons of each approach. Throughout the discussion, examples of successful destination branding practices are integrated.